(3MdjI GdChdjGA hWHbGJ GdCUajGAs - (3nCoHh ofnYje CMeO Hf YHO Gddg Hf CMeO GdCUHgGfj,J (B430 (3g` s
(3ChdgG (B:s
(3JQLeI bJGOI Hf OeGeI CHhGdNWGH s
(3BNQgG (B:s
(3JfJgi HJQLeI YHOGddg Hf hgH Hf efjg s
(3GdehLhO bWYI efgs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B282s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B117 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B698s
Keywords: (3GdJGQjNs